Multilocular Cystic Renal Cell Carcinoma or Cystic Nephroma? - Adolfo González-Serrano; Roberto Cortez-Betancourt; Alejandro Alías-Melgar; Pedro Jair Botello-Gómez; Emilio Ramírez-Garduño; Eric Iván Trujillo-Vázquez; Yosimart Torres-Santos; José Antonio Mata-Martínez; Fernando Carreño- de la Rosa (Case Reports in Urology)
The incidence of Multilocular cystic renal cell carcinoma (MCRCC) in literature is very low and confounding MCRCC with cystic nephroma (CN) is even more unusual. The aim of this report is to present a case of MCRCC and emphasize the importance of the preoperative radiologic evaluation and immunohistochemical staining confirmation to obtain an accurate diagnosis. A 73-year-old woman presented with a history of 4-month right flank pain. CT showed a Bosniak type III renal mass. After laparoscopic partial nephrectomy the initial report was cystic nephroma. Immunohistochemical staining was performed being positive for Epithelial Membrane Antigen thus changing the diagnosis to MCRCC. Multilocular cystic renal cell carcinoma cannot reliably be distinguished from cystic nephroma neither by physical examination nor by radiologic evaluation; immunohistochemical staining assay is useful to differentiate between these conditions allowing an accurate diagnosis and proper follow-up.